Διαγραμματική προσέγγιση της συνάρτησης προσφοράς του χρήματος - Γκότσης Χαράλαμπος (SPOUDAI Journal of Economics and Business, 2007)
The objective of this study is to develop the macroeconomic money supply function through the method of graphic presentation, given that the usually applied mathematical function is very restrictive, regarding the interpretation of the relevant parameters. On the contrary, the developed method of graphic presentation offers the following advantages: First, it presents clearly the relationships between money market and loan market. Second, it leads to the identification of the interrelationship of both supply and demand, during the determination of money supply and third, the results which are successively derived after potential variations of specific parameters of the monetary policy are rendered directly apparent.